THE INFLUENCE OF SERVANT LEADERSHIP AND EMPOWERMENT ON EMPLOYEE PERFORMANCE AT PT BANK CAPITAL INDONESIA, TBK - Eunike Catherine Lydiastuti; Tristiana Rijanti (LPPM STIE YKPN Yogyakarta, 2025)
The aim of this research is to examine the influence of servant leadership and employee empowerment, on employee performance at PT Bank Capital Indonesia Tbk. This research is motivated by the importance of effective leadership and empowered employees in driving individual and organizational success, particularly in the highly competitive banking industry. Given the limited research that specifically focuses on the combined influence of servant leadership and empowerment on employee performance in the context of Indonesian banking, this study aims to fill this knowledge gap. To achieve this, primary data was collected through questionnaires distributed to 116 employees at PT Bank Capital Indonesia, Tbk, with 100 respondents by purposive sample. The collected primary data was processed using SPSS 26 for Windows. The validity of the research instruments was tested using factor analysis, while reliability was measured using Cronbach's Alpha coefficient. Linear regression analysis was used to test the formulated hypotheses. The findings of this research indicate that servant leadership and employee empowerment have a positive and significant impact on employee performance at PT Bank Capital Indonesia, Tbk. The research can lead to substantial improvements in employee performance. The findings of this study are expected to contribute to the knowledge of academics and practitioners in the fields of leadership and human resource management. By highlighting the positive impact of servant leadership and employee empowerment, this research can be considered for implementing servant leadership and empowerment in order to improve employee performance. By fostering a culture of servant leadership and empowering employees to have a sense of ownership over their work, organizations can unlock the full potential of their workforce and achieve sustainable competitive advantage.